Case Report. Cryoglobulin Hyaline-thrombi Associated Acute Jejunitis in A Patient with Type 2 Cryoglobulinemic Glomerulonephritis. (28th October 2021) - Al-Othman, Y; Qu, Z; Zhang, P
Abstract: Introduction/Objective: Only one prior case report indicates that mixed positive cryoglobulin in serum can be associated with intestinal vasculitis (Annals of Internal Medicine, 1974). Methods/Case Report: We report a 63-year old man with history of positive serum cryoglobulin and hepatitis-C 4 years ago and membranoproliferative pattern of glomerulonephritis with possible cryoglobulin type of deposits by electron microscopy on renal biopsy. After treatment, his hepatitis C became negative. But he was recently found to have monoclonal IgM-kappa and positive cryoglobulin in his serum, and the concurrent renal biopsy showed membranoproliferative pattern of glomerulopathy with many hyaline-thrombi (eosinophilic vascular occlusions with no lamination, inflammatory cells or nuclear debris) in the glomerular capillary loops (Figure, left panel). Both immunofluorescent and electron microscopy confirmed a mixed IgG polyclonal and IgM monoclonal type 2 cryglobulinemic glomerulonephritis. The patient also developed abdominal pain and underwent intestinal endoscopy with biopsy. His jejunal biopsy revealed neutrophil infiltration into glands and surface epithelium, with superficial sloughed epithelial cells, consistent with acute jejunitis with features of ischemic etiology. In addition, hyaline-thrombi were identified in the submucosal vessels with surrounding vasculitis (Figure, right panel); the central part of thrombi was morphologically similar to that found in glomerular capillary loops. Therefore, we conclude that cryoglobulin associated hyaline-thrombi were the most likely etiology to cause the acute ischemic jejunitis in this patient. Results (if a Case Study enter NA): NA Conclusion: NA